Institutions, Innovations, and Growth - Huang, Haizhou; Xu, Chenggang (American Economic Review, 1999)
The fundamental importance of economic institutions for economic growth through their impact on technological change has long been argued by Joseph Schumpter and others. Recent empirical studies have reconfirmed such arguments. Robert Barro (1997) finds that economic and political institutions are the most important factors in explaining differences in growth across economies. New growth theory has made major breakthroughs in endogenizing technological changes. However, although some insightful and inspiring discussions of institutional impacts of innovation are provided, there is little attempt in these models to explain what, aside from capital, labor inputs, and knowledge accumulation, determines innovation. An attempt is made to fill the gap in literature by examining how financial institutions affect technological innovation and thus affect growth.